Chinese adolescents' coping tactics in a parent-adolescent conflict and their relationships with life satisfaction: the differences between coping with mother and father - Zhao, Hongyu; Xu, Yan; Wang, Fang; Jiang, Jiang; Zhang, Xiaohui; Wang, Xinrui (Frontiers in Psychology, 2015)
The present study examined the differences of conflict coping tactics in adolescents’ grade and gender and parents’ gender and explored the relationships among conflict frequency, conflict coping tactics and life satisfaction. A total of 1,874 Chinese students in grades 7, 8, 10 and 11 completed surveys on conflict frequency, coping tactics and life satisfaction. The results obtained by MANOVA suggested that the adolescents’ reported use of assertion and avoidance with either mothers or fathers increased from Grade 7 to Grade 8 and did not change from Grade 8 to Grade 11 in parent-adolescent conflicts. The results of paired sample T tests indicated that adolescents used more conciliation in Grade 7, more conciliation and assertion in Grade 8, and more conciliation and less avoidance in Grade 10 and 11 to cope with mothers than with fathers in parent-adolescent conflicts. Boys used more conciliation and less avoidance, while girls used more conciliation, assertion and third-party intervention to cope with mothers than with fathers in parent-adolescent conflicts. The results of the hierarchical regression analysis indicated the significance of the primary effects of conflict frequency and coping tactics on life satisfaction. Specifically, conflict frequency negatively predicted life satisfaction. Conciliation positively and avoidance negatively predicted life satisfaction when adolescents coped with either mothers or fathers in parent-adolescent conflicts. Assertion negatively predicted life satisfaction when adolescents coped with fathers. The moderating effects of conflict coping tactics on the relationship between parent-adolescent conflict frequency and life satisfaction were not significant.